2020
DOI: 10.1111/jgs.16434
|View full text |Cite
|
Sign up to set email alerts
|

Depression Symptoms and Cognitive Test Performance in Older American Indians: The Strong Heart Study

Abstract: BACKGROUNDAmerican Indians have excess risk of depression, which can contribute to cerebrovascular and cognitive disability, with effects on memory, processing speed, executive function, and visuospatial ability. However, studies examining depression and cognition in American Indians are limited; this study aims to report associations of depression with general cognition, verbal fluency and memory, and processing speed.DESIGNCohort study.SETTINGThe Cerebrovascular Disease and its Consequences in American India… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…48,49 Depression: In these analyses, we identified common symptoms of depression, which may influence test scores. Prior studies in this cohort have found approximately 20% of older American Indians met criteria consistent with clinical depression (CES-D score >16), 34 and that depressive symptoms were associated with poorer processing speed, verbal fluency, general cognition, and lower body motor function, independent of age, sex, education, income, married status, alcohol use, smoking, hypertension, diabetes, and stroke. Our research group also found that 12 of the 20 questions had adequate psychometric properties.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…48,49 Depression: In these analyses, we identified common symptoms of depression, which may influence test scores. Prior studies in this cohort have found approximately 20% of older American Indians met criteria consistent with clinical depression (CES-D score >16), 34 and that depressive symptoms were associated with poorer processing speed, verbal fluency, general cognition, and lower body motor function, independent of age, sex, education, income, married status, alcohol use, smoking, hypertension, diabetes, and stroke. Our research group also found that 12 of the 20 questions had adequate psychometric properties.…”
Section: Discussionmentioning
confidence: 72%
“…The Centers for Epidemiologic Studies Depression (CESD) Scale assessed symptoms of depression. 34 Participants self-reported age (years), sex (male or female), years of formal education, having smoked more than 100 cigarettes in lifetime (yes or no), alcohol use patterns, including any use in past month (yes or no), bilingual status (self-reported moderate or better ability to speak Native language, in addition to study requirement of English fluency), prior neurological symptoms including temporary or sustained loss of speech, loss of vision, double vision, numbness, paralysis, or extreme dizziness; prior traumatic brain injury both with or without loss of consciousness; and prior stroke. Hypertension was defined based on measured, averaged, seated systolic blood pressure ≥140 mmHg, diastolic blood pressure ≥90 mmHg, and/or use of antihypertensive medications; diabetes mellitus by fasting blood glucose ≥126 mg/dL and/or use of antiglycemic medications or insulin; chronic kidney disease as estimated glomerular filtration rate <60 mL/min using the CKD-EPI 2009 equation; body mass index as weight in kilograms divided by height in meters squared.…”
Section: Mri Protocolsmentioning
confidence: 99%
“…Given the variability across tribal communities within the United States and across Indigenous populations in Northern America, we advocate for additional psychometric research on the CES-D. While we have assessed convergent validity of the 20-item CES-D with age, gender, education, income, marital status, alcohol use, smoking, hypertension, diabetes, stroke, processing speed, general cognition, verbal fluency, and motor function in the CDCAI study (Suchy-Dicey et al, 2020), we have not assessed convergent and discriminant validity of the 12-item CES-D scale. We propose this as future work to be done after approval from the tribal councils.…”
Section: Discussionmentioning
confidence: 99%
“…A steep decline in scores was observed after 75 years of age. Summary cognitive test scores for this cohort suggest that cognitive test score distributions are overall lower in American Indian adults compared with majority populations (Suchy-Dicey, Verney, et al, 2020), with study medians near or below conventional thresholds used to define cognitive impairment or dementia in NHW (Adesope et al, 2010; Barry et al, 2008; Loonstra et al, 2001). Whether a majority of individuals score proportionally lower than their peers from the majority population due to the influence of sociodemographic and health disparities, or whether some unidentified subset of individuals with clinically significant cognitive syndromes is lowering the population-wide estimates is yet unknown.…”
Section: Cowa Performance In American Indiansmentioning
confidence: 92%
“…However, many minoritized populations, such as American Indians, have not been systematically included in psychometric evaluations of most standard tests, and when minority groups differ meaningfully from the majority in either diagnostic or normative standards, such oversights are likely to preclude clinicians and researchers from making valid diagnostic inference (Kiselica et al, 2021; Manly et al, 1998; Pedraza et al, 2012; Rivera Mindt et al, 2010). Given high risk of vascular and Alzheimer’s-related cognitive injury in American Indians (Mehta & Yeo, 2017; Suchy-Dicey et al, 2021; Suchy-Dicey, Howard, et al, 2022; Zhang et al, 2008), and clear disparities in cognitive test performance, compared with the majority population (Suchy-Dicey, Verney, et al, 2020; Suchy-Dicey et al, 2022; Verney et al, 2019), formal psychometric evaluation of cognitive tests is critically needed for this vulnerable population.…”
mentioning
confidence: 99%